Valdosta Project Change, Scrapbook, October 1998 - Valdosta Project Change (Lowndes County Historical Society, 1998)
10/1- Report cards are in for middle and elementary- Patricia H. Croll; 10/3- Valdosta family upset over county jail’s suicide attempt policy- Jodi M. Scott; 10/7- Raising the bar for state education: New standards for local boards of education announced today- Patricia H. Croll; 10/8- Why blacks stand by Clinton- Bill Maxwell; 10/10- Trio awarded $1 million in shoplifting racism case- Joann Loviglio; 10/10- Ability, not color of skin, should matter most- Bill Malone, Valdosta; 10/11- Work progresses on Weed and Seed- Jodi M. Scott; 10/12- Rally stirs calls for justice: Second march planned to protest inmate’s death- Patricia H. Croll; 10/13- VBOE seeks community input: Allen goes to school to talk with parents- Patricia H. Croll; 10/14- We’ve come a long way but it’s a long road ahead- Charles Moore; 10/16- Take a stand- no author; 10/16- PBS miniseries chronicles America’s journey through slavery- no author; 10/16- March splits local rights activists- Joe Dunlop; 10/18- Protesters take to city’s streets: Hundreds decry conditions at jail- Jodi M. Scott; 10/19- Rights activists forming tribunal: Rose attending council meeting- Jodi M. Scott; 10/21- It’s not going away- no author; 10/21- We need to end uneasiness in our Black Community- Bill Maxwell; 10/23- Wait for probe results: Mayor urges Rose to be patient- Shelby G. Spires ; 10/28- Crime lab done with inmate death: Local officials await report before coroner’s inquest held in November- Jodi M. Scott;
Valdosta Project Change. “Valdosta Project Change Scrapbook, October 1998. Lowndes County Historical Society, repository. Digital Copy--Valdosta State University Archives and Special Collections, MS-181: Valdosta Project Change Collection, 1997-2003. 1 PDF document and scans, 22 pages. 144 MB (151,011,527 bytes).
Keywords: Clippings (Books, newspapers, etc.); Discrimination--Prevention; Lowndes County Historical Society (Valdosta, Ga.); Nonprofit organizations; Project Change; Race discrimination--Prevention; Racism; Scrapbooks; Valdosta (Ga.) -- Social conditions; Valdosta (Ga.); Valdosta Daily Times; Valdosta Project Change